The discourses of self and identity: a Levinasian approach to rethinking discourse. Issue 3 (4th May 2022) - Blumenfeld-Jones, Donald
ABSTRACT: The distinction between 'self' and 'identity' is explored using James Baldwin's work and Western anthropology's assignment of 'self' only to Western dominant cultures. Anthropologists perform epistemicide on these 'less advanced' cultures by reducing them to identification with the group with no inner life. Identity is then explored as an artifact of language through de Saussure, Derrida, and Foucault. Emmanuel Levinas' analysis of how we craft identities (through discourse) departs from discourse through a self (transcendent and unclassifiable through language). Levinas' approach to ethics depends on what language cannot deliver, an awareness of an Other as radically separate. The Other escapes linguistic machinations and establishes our individual identities. Responsibility emerges for the infinite Other by recognizing we cannot control another. Ironically, we are connected to an Other through humility of not knowing the Other which fulfills our desire for knowing (by not knowing), what Levinas terms 'metaphysical desire'.